Senior High School Students’ Perception of Using Wordwall Toward Their Motivation In Learning Vocabulary - Hafifah, Aura; Hanifa, Rizaldy (Universitas Negeri Padang, 2024)
This study aims to find out what students' perceptions of the use of wordwall as a learning media on vocabulary learning motivation. This study used descriptsive research design with quantitative descriptive approach. The research participants were 64 students of senior high school levels from two classes in the 2023/2024 academic year. The data were collected by using questionnaire base on ARCS theoretical motivation model. The findings showed that most of the students had very high motivation in using wordwall in English vocabulary learning concerning attention, confidence, satisfaction and relevance aspects. In addition, the findings revealed they feel enthusiastic and motivated by the use of wordwall which offers a variety of word games equipped with various features including audio, images, ranking scores, moving animations. Therefore, teachers are highly recommended to use learning media such as wordwall in the process of learning English vocabulary. In addition, it is suggested for students to be able to utilize wordwall to learn vocabulary autonomously while playing in and out of the classroom. Furthermore, future researchers may implement wordwall in various other language skills.